Sustainable spiritual tourism experience: Transforming melukat ritual in Sawan Village, Bali - Luh Putu Triyanti Ariestiana Dewi; I Gede Putra Nugraha (International Journal of Applied Sciences in Tourism and Events, 2026)
This study explores the transformation of the Melukat ritual into a spiritual tourism experience and examines its contribution to sustainable tourism development in Sawan Village. A qualitative approach was employed using purposive sampling to select key informants, including local community members, traditional leaders, temple stakeholders, and tourism actors involved in or knowledgeable about the Melukat ritual at Pura Batu Bolong. Data were collected through field observations, in-depth semi-structured interviews, and document analysis, and were analyzed using inductive thematic analysis. The findings reveal that the Melukat ritual can be systematically transformed into a spiritual tourism experience through the preservation of ritual authenticity, community-based governance, and active tourist participation. The ritual generates transformative experiences, including purification, emotional healing, inner peace, and self-reflection, which attract both domestic and international tourists seeking meaningful and spiritually enriching journeys. These experiences contribute to spiritual sustainability by safeguarding the sacredness of holy water and the spirit of place, while simultaneously supporting sustainable rural development through cultural preservation, environmental conservation, and local economic opportunities. Nevertheless, its tourism potential remains underdeveloped due to limited promotion, weak destination management, and the absence of structured governance and carrying-capacity regulations. This study contributes to spiritual tourism literature by proposing an integrated framework linking ritual transformation, transformative tourist experiences, spiritual sustainability, and sustainable rural development. The findings also offer practical insights for local stakeholders to design tourism experiences that maintain ritual sacredness while enhancing community welfare and destination competitiveness.